Determinan Ketimpangan Pendapatan Pasca Covid-19 di Sulawesi Tenggara - Salsa Amelia Azzahra; Basri Bado; Irwandi Irwandi; Sri Astuty; Muhammad Syafri (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
The COVID-19 pandemic that struck the world caused a multisectoral crisis, weakened economic growth, and limited people's ability to carry out daily activities. Weakening growth led to a decline in per capita income, which in turn exacerbated income inequality. Income inequality is reflected by the Gini ratio index. In Southeast Sulawesi, the Gini ratio index increased during the COVID-19 pandemic and was consistently higher than the Gini ratio indices for Sulawesi Island and the national average. Therefore, this study aims to examine how economic growth, poverty, unemployment, the Human Development Index (HDI), and infrastructure impact income inequality in post-COVID-19 Southeast Sulawesi. This study employs a quantitative method, using secondary data from 2023 for each district/city in Southeast Sulawesi, obtained from the Central Bureau of Statistics (BPS). The analysis was conducted using the Ordinary Least Squares (OLS) method with Eviews 12 software. The results of the study indicate that, partially, the variable of economic growth has a negative and significant effect on income inequality in post-COVID-19 Southeast Sulawesi. The poverty variable has a negative but insignificant effect on income inequality. The unemployment variable has a positive but insignificant effect on income inequality. Meanwhile, the variables of the Human Development Index and infrastructure have positive and significant effects on income inequality. Simultaneously, economic growth, poverty, unemployment, the Human Development Index, and infrastructure collectively influence income inequality in post-COVID-19 Southeast Sulawesi.